First, let's evaluate |-4b-8|+|-1-b^2|+2b^3 when b=-2.
With b=-2, |-4b-8| becomes |-4(-2)-8| = |8-8| = |0| = 0.
Next, let's evaluate |-1-b^2|. When b=-2, |-1-b^2| becomes |-1-(-2)^2| = |-1-4| = |-5| = 5.
Finally, let's evaluate 2b^3. When b=-2, 2b^3 becomes 2(-2)^3 = 2(-8) = -16.
Now, let's substitute these values back into the original expression:
|-4b-8|+|-1-b^2|+2b^3 = 0 + 5 + (-16) = 5 - 16 = -11.
Therefore, |-4b-8|+|-1-b^2|+2b^3 equals -11 when b=-2.
Evaluate the expression for the given value of the variable.
|-4b-8|+|-1-b^2|+2b^3;b=-2
1 answer